A meta-analysis of potential ecological risk evaluation of heavy metals in sediments and soils - Vinod Kumar; Shevita Pandita; Raj Setia (Gondwana Res., 2022)
Heavy metals (HMs) contamination in soils and sediments (river/marine) and its impact on human health have induced a global consideration due to their bioaccumulation, non-biodegradability, toxicity and perseverance. The ecological risk assessment of HMs in soils and sediments have well studied in different countries, however there are very few studies in which ecological risk assessment of HMs has been compared in different countries. Therefore, the ecological risk of HMs (As, Cd, Co, Cr, Cu, Hg, Mn, Ni, Pb and Zn) in soils and sediment was assessed using the studies published during 2020 and 2021. The available data was for 308 sediment sampling sites in 17 countries (Australia, Azerbaijan, Bangladesh, China, Colombia, Egypt, Greece, India, Iran, Kenya, Malaysia, Mexico, Saudi Arabia, Sri Lanka, Nigeria, Pakistan and Turkey) and for 799 soil sampling sites in 17 countries (Belgrade, Brazil, Chile, China, Egypt, India, Iran, Ireland, Mongolia, Morocco, Nigeria, Oman, Pakistan, Poland, Southern Africa, Thailand and Turkey). Among all the sediment and soil sampling sites, majority of the sites were recorded from China and Ireland, respectively. The impact of HMs on the environment was studied using Potential Ecological Risk Evaluation (PERI). The results of PERI showed the highest concentration of Cd and Hg in soils and sediments among all the HMs. The highest PERI values of HMs in sediments and soils were recorded in India and Poland, respectively. Principal component analysis (PCA) of sediments and soils showed that India and Colombia represented one PC, whereas the remaining countries were included in the similar group. The sampling sites were categorised into different climates based on the Koppen climate classification and PCA showed that PC1 is mainly controlled by Cu, Zn and Ni for sediments, and Pb for soils along with other metals, irrespective of the climate. This review provides the latest information about the PERI data of HMs in soils and sediments, which will be useful for taking strategic management measures to control the contaminations of HMs in sediments and soils, thereby management of water and soils resources of a country and the world. (c) 2021 International Association for Gondwana Research. Published by Elsevier B.V. All rights reserved.
Keywords: Digital; Mental health care; Tele psychiatry